University Course Timetabling System For Part-Time Students - Ruslaan, Mohd Asyraf; Zakaria, Zalmiyah; Saringat, Mohd Zainuri; Kasim, Shahreen (International Journal of Advanced Science Computing and Engineering, 2019)
University timetabling system is a part of a timetabling problem that aims to produce course timetable that meets student needs such as the maximum number of subjects that can be offered, the maximum number of elective subjects that can be offered and the number of subject students can take. In every semester, the timetabling process in UTMSPACE is done manually where there are likely to be a small number of students who will have problems because the subject to be taken is not in the subjects offering list. Additionally, the number of subjects offered is also not optimal and this will result in a loss on UTMSPACE because each subject is offered at a cost. Therefore, in order to solve this problem, the Heuristic-based approach is used to overcome the problems mentioned and speed up the process to generate timetable. Heuristic engines have been developed using PHP language programming. This approach has been successfully tested and implemented using real-time scheduling data at UTMSPACE for Software Engineering course. The results show that Heuristics has successfully solved the problem of producing a timetable without affecting students who want to enroll the subject offered.